Specific Posture-Stabilising Effects of Vision and Touch Are Revealed by Distinct Changes of Body Oscillation Frequencies - Sozzi, Stefania; Nardone, Antonio; Schieppati, Marco (Frontiers in Neurology, 2021)
We addressed postural instability during stance with eyes closed (EC) on a compliant surface in healthy young people. Spectral analysis of centre of foot pressure oscillations was used to identify the effects of haptic information (light-touch, EC-LT) or vision (eyes open, EO) or both (EO-LT). Spectral median frequency was strongly reduced by EO and EO-LT, while spectral amplitude was reduced by all ‘stabilising’ sensory conditions. Reduction in spectrum level by EO mainly appeared in high-frequency range. Reduction by LT was much larger than that induced by vision in low-frequency range, less so in high-frequency range. Touch and vision together produced a fall in spectral amplitude across all windows, more so in AP direction. Lowermost frequencies contributed poorly to geometric measures (sway path and area) for all sensory conditions. The same subjects participated in control experiments on a solid base of support. Median frequency and amplitude of the spectrum and geometric measures were largely smaller when standing on solid than on foam base, but poorly affected by the sensory conditions. Frequency analysis but not geometric measures allowed to disclose unique tuning of the postural control mode by haptic and visual information. During standing on foam, vision did not reduce low-frequency oscillations, while touch diminished the entire spectrum, except for the medium-high frequencies, as if sway reduction by touch would rely on rapid balance corrections. The combination of frequency analysis with sensory conditions is a promising approach to explore altered postural mechanisms and prospective interventions in subjects with central or peripheral nervous system disorders.